Purchasing power parity and the European single currency: some new evidence - Maria Christidou; Theodore Panagiotidis (TÜSİAD-Koç University Economic Research Forum, 2010)
The effect of the single currency on the Purchasing Power Parity (PPP) hypothesis is examined in this study for the 15 EU countries, vis a vis the US dollar, before and after the advent of the euro. Standard as well as nonlinear unit root tests are employed on the time series dimension. Unit root tests reject PPP and the highest half-lives are observed after the introduction of the single currency. Panel unit root (Pesaran, 2007) and stationarity tests (Hadri and Kurozumi, 2008) that take into account cross-sectional dependence are also estimated. The results remain inconclusive as panel stationarity tests fail to support PPP whereas panel unit root tests fail to reject PPP for the whole sample and for the period before the introduction of the single currency.
Keywords: F31; F33; G15; 330; Purchasing Power Parity; half-life; nonlinear unit roots; panel unit roots; heterogeneity; cross-section dependence; Kaufkraftparität; Euro; US-Dollar; Unit Root Test; Nichtlineares Verfahren; Panel; EU-Staaten